2010
DOI: 10.1080/19361521003761325
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of MASTR EMDR Therapy for Traumatized Adolescents

Abstract: This study examined MASTR/EMDR, a trauma-focused treatment for traumatized youth taken in charge by youth protective services. Participants were 40 adolescents who were exhibiting conduct problems and internalizing and externalizing behaviors and who had been exposed to maltreatment. Participants were randomly assigned to MASTR/EMDR treatment or to a routine care condition. Self-report questionnaires and semistructured interviews were administered to participants and one of their parents/caregivers at three po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 53 publications
1
43
1
2
Order By: Relevance
“…As with residential studies, therapists' in secure facilities perceived a range of gains for youth who experienced FTM (Farkas et al 2010). Similar to youth reports in Barron and Tracey's (2017) cluster case study in a secure facility, youth were perceived by therapists in the current study to made gains in motivation, stabilization, problemsolving, anticipating risks, and imagining more hopeful futures .…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…As with residential studies, therapists' in secure facilities perceived a range of gains for youth who experienced FTM (Farkas et al 2010). Similar to youth reports in Barron and Tracey's (2017) cluster case study in a secure facility, youth were perceived by therapists in the current study to made gains in motivation, stabilization, problemsolving, anticipating risks, and imagining more hopeful futures .…”
Section: Discussionsupporting
confidence: 68%
“…FTM as a whole package has been evaluated and found to be a supportive experience that leads to positive outcomes for youth. Within the residential setting, symptoms of posttraumatic stress and incidents of violence have halved and discharge rates from residential to community care doubled (Farkas et al 2010;Greenwald et al 2012). Mental health and behavioral gains for abused youth have maintained at 3 months and 6 month follow-up (Farkas et al 2010;Greenwald 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of the three studies 106-109 using CBT to specifically target physical abuse, all three measured some form of behavioural outcomes, two studies [107][108][109] Of the two studies 120,121 that used EMDR, both looked at psychological distress, and one study 120 also measured behaviour outcomes.…”
Section: Cognitive-behavioural Therapy Interventionsmentioning
confidence: 99%
“…Nine randomised trials of CBT or enhanced CBT interventions were identified [110][111][112][114][115][116][117]120,121 that were designed to address the consequence of maltreatment, irrespective of maltreatment type. The studies were themselves heterogeneous, and fall into four broad categories:…”
Section: Economic Evidencementioning
confidence: 99%